2009
DOI: 10.1055/s-0029-1224799
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of the African American Periorbital Area: Dynamic Considerations

Abstract: The rejuvenation of the African American periorbit is rooted in select modifications of traditional techniques. The African American patient presents with dynamic considerations and needs. Whereas this subset is at risk for pigmentation and scar concerns, the natural resistance to actinic damage makes rejuvenation efforts rewarding. We will review the composite that makes up the periorbit, the brow, upper eyelid, lower eyelid/ lateral canthus, and the midface unique. Specific indications and presurgical and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Avoidance of suture scars requires careful suture selection, especially in African American patients. For example, the use of prolene suture as a mechanism to avoid suture scars in African American patients undergoing periorbital surgery has been described 27 . As such, scar scales that incorporate suture scar assessment may guide the optimisation of cosmetic surgery in dark‐skinned individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidance of suture scars requires careful suture selection, especially in African American patients. For example, the use of prolene suture as a mechanism to avoid suture scars in African American patients undergoing periorbital surgery has been described 27 . As such, scar scales that incorporate suture scar assessment may guide the optimisation of cosmetic surgery in dark‐skinned individuals.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the use of prolene suture as a mechanism to avoid suture scars in African American patients undergoing periorbital surgery has been described. 27 As such, scar scales that incorporate suture scar assessment may guide the optimisation of cosmetic surgery in dark-skinned individuals. However, the Fitzpatrick level and race/ethnicity of the SBSES validation studies were not reported.…”
Section: Stony Brook Scar Evaluation Scalementioning
confidence: 99%
“…20 Few reports that 6-0 nylon leaves virtually no track marks in skin of color. 21 To further reduce track marks, a running subcuticular suture with polypropylene is preferred to a simple running whenever possible.…”
Section: Suture Selection In Skin Of Colormentioning
confidence: 99%